2020
DOI: 10.1186/s12885-020-6608-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers of ductal carcinoma in situ progression

Abstract: Background: Ductal carcinoma in situ is a non-obligate precursor of invasive breast carcinoma and presents a potential risk of over or undertreatment. Finding molecular biomarkers of disease progression could allow for more adequate patient treatment. We aimed to identify potential biomarkers that can predict invasiveness risk. Methods: In this epithelial cell-based study archival formalin-fixed paraffin-embedded blocks from six patients diagnosed with invasive lesions (pure invasive ductal carcinoma), six wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…After a 5year follow up, the primary tumors were analyzed in a first step with the "PanCancer Progression Panel" from NanoString. This panel has been shown previously to comprehensively characterize genes involved in tumor progression and metastasis of solid tumors [19,20]. Subsequently, the multidimensional PCA revealed a distinct expression pattern of the analyzed genes throughout the defined groups and the most homogenously expressed gene was CIB1.…”
Section: Discussionmentioning
confidence: 92%
“…After a 5year follow up, the primary tumors were analyzed in a first step with the "PanCancer Progression Panel" from NanoString. This panel has been shown previously to comprehensively characterize genes involved in tumor progression and metastasis of solid tumors [19,20]. Subsequently, the multidimensional PCA revealed a distinct expression pattern of the analyzed genes throughout the defined groups and the most homogenously expressed gene was CIB1.…”
Section: Discussionmentioning
confidence: 92%
“…Although we have proposed possible progression markers that will require more extensive validation, it still remains to be seen whether, and how, each of these may play a role in this disease. A recent study 7 also looking at potential biomarkers of DCIS progression, identified the genes FGF2 , GAS1 and SFRP1 as being markers of in situ progression, suggesting their downregulation contributed to the invasiveness of epithelial cells. In support of this we also see that these 3 genes are notably down regulated as samples are arrayed along the timeline.…”
Section: Resultsmentioning
confidence: 99%
“…2A). Gene Ontology (GO) term analysis on these two networks revealed an enrichment for upregulated (in IDC over DCIS) genes involved in both extracellular matrix (EM) organisation Fold Enrichment;29) and cell adhesion (FDR 1.8E-6, Fold Enrichment; 7) and down-regulated genes associated with both epidermis development Fold Enrichment;18) and epithelial development Fold Enrichment;7). Specific genes included in each cluster network are frequently associated with these processes, such as FN1 (Fibronectin) and the collagen genes (COL1A2, COL1A1, COL12A, COL3A1, COL5A2).…”
Section: Two Gene Network Dominate Expression Differences Between Co-...mentioning
confidence: 99%
“…2 The intervention of breast precancerous lesions and blocking its development to breast cancer is the key to the prevention and treatment of breast cancer. 8 Xihuang Pill (XHP) is a traditional Chinese herbal formula, which is published in "waike zhengzhi quansheng ji". It consists of NIU HUANG, SHE XIANG, RU XIANG (vinegar), and MO YAO (vinegar).…”
Section: Introductionmentioning
confidence: 99%
“… 2 The intervention of breast precancerous lesions and blocking its development to breast cancer is the key to the prevention and treatment of breast cancer. 8 …”
Section: Introductionmentioning
confidence: 99%